Teachers' implementation of socio-scientific issues-based approach in teaching science: A needs assessment - Jeah May Badeo; Domarth Ace Duque; Russel L. Arnaldo (OmniaScience, 2024)
This study made a preliminary attempt to conduct a needs assessment of teachers' implementation of the SSI-based approach in teaching Science by exploring Filipino teachers' awareness, perceived need, readiness, and willingness. It also aimed to determine which among the demographic profile of the teachers had significant differences in their perceived need and readiness. A needs assessment using a quantitative survey research design was employed in this study. The data-gathering procedure was done using a validated online survey questionnaire with a Cronbach alpha of 0.89. A total of 124 science teachers took part in this study throughout the two-week implementation. The gathered data were analyzed using descriptive and inferential statistics. Results showed that more than half of the teachers were highly aware of the SSI-based approach and perceived the need for its implementation in science classes. Teachers were also willing to participate in an SSI training program to learn more about it and develop their own SSI-related materials. Furthermore, gender and specialization significantly differed in teachers' perceived need, while specialization significantly differed in readiness. This study can be used as a basis for further research on teachers' perceptions and views of implementing the SSI-based approach.